Answers

2015-01-04T18:32:48+05:30
See your first equation will be x+7y = -11 and second will be 3x-5y=6 
and by multiplying 3 in eqn.1 nad subtracting from 2 y=-3/2 and then x =-1/2
0
2015-01-04T18:34:55+05:30
In equation 1 x/7+11/7=-y =&x+11=-7y =& x=-7y-11......3 In eq 2 x-5y/3=2 3x-5y=6 x=(6+5y)/3....4 Now from eq 3&4 -11-7y=(6+5y)/3 -33-21y=6+5y 26y=-39 y=-39/26 =-3/2 Substitute value of y in eq 4 x=(6+5×-3/2)/3. {Take -3/2 as -1.5) =(6-7.5)/3 =-1.5/3 =-1/2
0
Thanks so much
Sorry I had to correct
Got confused that it was (x-5y)/3 instead of x-5y/3
Had to correct the process
And please if the answer has been helpful mark it as best ,I need to gain a rank